Analisis Upaya Hukum Yang Dapat Dilakukan Oleh Korban Salah Tangkap - Putri, Abelia Zahara; Siswanto, Heni; Fathonah, Rini; Rosidah, Nikmah; Amrullah, Rinaldy (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Legal protection for victims of wrongful arrest is regulated in Articles 95 to 97 of the Indonesian Criminal Procedure Code (KUHAP) and further detailed in Government Regulation No. 92 of 2015 concerning compensation and rehabilitation mechanisms. This study aims to examine the forms of legal protection available to victims of wrongful arrest and to analyze the legal remedies they can pursue to claim their rights. The research employs a normative and empirical legal approach. The normative approach is based on statutory regulations, literature, and academic references, while the empirical data is collected through interviews with relevant informants. The findings indicate that victims of wrongful arrest are entitled to compensation and rehabilitation through legal mechanisms such as pretrial motions. These efforts are intended to restore the dignity, rights, and legal status of the victims. However, in practice, challenges remain in the enforcement of such rights due to procedural complexity and the lack of legal assistance. The study recommends that legal protection should be ensured from the earliest stages of investigation to prevent arbitrary treatment by law enforcement. Furthermore, access to legal remedies must be simplified, and legal aid should be provided to ensure justice for victims.